2010
DOI: 10.1113/jphysiol.2010.187112
|View full text |Cite
|
Sign up to set email alerts
|

RAPID REPORT: Anin vivotethered toxin approach for the cell-autonomous inactivation of voltage-gated sodium channel currents in nociceptors

Abstract: Understanding information flow in sensory pathways requires cell-selective approaches to manipulate the activity of defined neurones. Primary afferent nociceptors, which detect painful stimuli, are enriched in specific voltage-gated sodium channel (VGSC) subtypes. Toxins derived from venomous animals can be used to dissect the contributions of particular ion currents to cell physiology. Here we have used a transgenic approach to target a membrane-tethered isoform of the conotoxin MrVIa (t-MrVIa) only to nocice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 34 publications
0
32
0
2
Order By: Relevance
“…Recordings from single units were made as previously described 52,53 , however, we applied cooling stimuli (Peltier device) with almost identical amplitudes and kinetics to those employed in behavioral training paradigms and cortical recordings. Two cooling ramps were routinely applied, 32-22 ˚C to probe for low-threshold units and a second 32-12 ˚C stimulus to characterize high-threshold responders and suprathreshold firing of coldsensitive fibers.…”
Section: Skin-nerve Preparation and Sensory Afferent Recordingsmentioning
confidence: 99%
“…Recordings from single units were made as previously described 52,53 , however, we applied cooling stimuli (Peltier device) with almost identical amplitudes and kinetics to those employed in behavioral training paradigms and cortical recordings. Two cooling ramps were routinely applied, 32-22 ˚C to probe for low-threshold units and a second 32-12 ˚C stimulus to characterize high-threshold responders and suprathreshold firing of coldsensitive fibers.…”
Section: Skin-nerve Preparation and Sensory Afferent Recordingsmentioning
confidence: 99%
“…However gene deletion of Nav1.8 leads to increased Nav1.7 channels and TTX-sensitive currents in nociceptors of Nav1.8 knockout mice [19] making it difficult to interpret the single contribution of each channel type to pain modalities (inflammatory, neuropathic acute pain or cold pain). To address this, we genetically delivered t-MrVIa μO-conotoxin (preferential blocker of Na v 1.8) to nociceptors by mouse BAC transgenesis [12]. Electrophysiological analyses showed that the t-toxin inhibited TTX-R Na + currents at the membrane, as it was released by enzymatic cleavage of the GPI anchor [12].…”
Section: Application Of T-toxins To the Dissection Of Mammalian Circuitsmentioning
confidence: 99%
“…To address this, we genetically delivered t-MrVIa μO-conotoxin (preferential blocker of Na v 1.8) to nociceptors by mouse BAC transgenesis [12]. Electrophysiological analyses showed that the t-toxin inhibited TTX-R Na + currents at the membrane, as it was released by enzymatic cleavage of the GPI anchor [12]. Behaviorally, t-toxin transgenic mice displayed reduced inflammatory and cold pain perception [12].…”
Section: Application Of T-toxins To the Dissection Of Mammalian Circuitsmentioning
confidence: 99%
See 2 more Smart Citations